Mastodon - Minnick, Chris; McCallister, Michael (--For dummies., 2023)
Ready to escape the drama of existing social media platforms and try something new and awesome in the world of social media? In Mastodon For Dummies, experienced tech trainers Chris Minnick and Mike McCallister show you exactly how to use Mastodon, the hot decentralized social media offering on the web and destination for thousands of social media migrants. Learn how to sign up for the service on your choice of server and get familiar with the rules of what's sure to become your new favorite app. You'll discover how to connect with other people, attract your own followers, and make yourself right at home in the Mastodon community. In the book, you'll find: easy-to-follow instructions on how to choose the Mastodon server that suits you best; instructions for establishing new connections on a new social platform and learning the rules of the road; tips for conducting business on Mastodon and making a home for your home-based business or brand on the social media service; and step-by-step guides on launching your very own server. Mastodon For Dummies is a must-listen if you're ready to leave old social platforms in the rearview and try something new.